Brain Stem Cavernous Malformations: Operative Nuances of a Less-Invasive Resection Technique. Issue 2 (8th December 2017) - Singh, Harminder; Elarjani, Turki; da Silva, Harley Brito; Shetty, Rakshith; Kim, Louis; Sekhar, Laligam N
Abstract: BACKGROUND: Different operative techniques are reported for the resection of brainstem cavernous malformations (BSCMs). The senior author has previously reported on a less-invasive technique of entering the brain stem with piecemeal removal of BSCMs, especially the deep-seated ones. OBJECTIVE: To present a larger series of these lesions, emphasizing the approach to the brain stem via case selection. We discuss the nuances of the less-invasive operative technique through case illustrations and intraoperative videos. METHODS: A retrospective review of 46 consecutive cases of BSCMs, with their clinical and radiographic data, was performed. Nine cases were selected to illustrate 7 different operative approaches, and discuss surgical nuances of the less-invasive technique unique to each. RESULTS: Postoperative morbidity, defined as an increase in modified Rankin Scale, was observed in 5 patients (10.9%). A residual BSCM was present in 2 patients (4.3%); both underwent reoperation to remove the remainder. At follow-up of 31.1 ± 27.8 mo, 3 patients experienced recurrence (6.5%). Overall, 65% of our patients improved, 20% stayed the same, and 11% worsened postsurgery. Two patients died, yielding a mortality of 4.3%. CONCLUSION: Using the less-invasive resection technique for piecemeal BSCM removal, in appropriately selected patients, has yielded comparable to improved patient outcomes over existing large series. In our experience, lateral, anterolateral, and posterolateral approaches are favorable over direct midline (dorsal or ventral) approaches. A thorough understanding of brain-stem safe-entry zones, in conjunction with appropriate approach selection, is key to a good outcome in challenging cases.